Pengembangan media puzzle pohon tubel untuk keterampilan membaca siswa sekolah dasar - Maryatri, Putri Ragil; Sudigdo, Anang; Anafiah, Siti (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This study aims to: 1) describe the needs of teachers and students regarding the development of the Puzzle Pohon Tubel media; 2) describe the development process of the Puzzle Pohon Tubel media; 3) determine the feasibility of the Puzzle Pohon Tubel media; and 4) determine students’ responses to the Puzzle Pohon Tubel media in early reading skills. This research is a research and development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were first-grade students of SD Negeri Turi 3 Sleman. The object of this research is the Puzzle Pohon Tubel media, which was designed as a learning tool to support early reading instruction. Data collection techniques included observation, interviews, questionnaires, and documentation. Data analysis techniques used both qualitative descriptive and quantitative descriptive analysis. The results show that: 1) the Puzzle Pohon Tubel media was successfully developed according to the needs of students and teachers; 2) the media is highly feasible based on expert validation, with scores of 94.64% from material experts, 92.13% from media experts, and 98.15% from teacher assessments; 3) students’ responses were in the “very good” category with a score of 93.15%. The media helps increase student enthusiasm and supports interactive and enjoyable learning.